Radiation-induced endometrial cancer after cervical carcinoma - Cavazza,Maria Carlota (2020)
Overview and Aims: Cases of radiation-induced endometrial cancer after cervical carcinoma are characteristically different than sporadic cases of endometrial cancer as they tend to be more aggressive, diagnosed in a more advanced stage, and with a poorer outcome. Therefore, it is important to maintain surveillance, be aware of the warning signs and know how to approach these secondary cancers in order to assure the best outcome for these patients. The goal of our study is to describe a case series of patients with radiation-induced endometrial cancer after cervical carcinoma followed at our institution. Study design: Retrospective, cross-sectional study. Population: Patients with a diagnosis of endometrial cancer who had previously received definitive radiation treatment for cervical cancer. Four patients met our inclusion criteria. Methods: Analyzed parameters included patient demographics, age upon diagnosis, type of radiation therapy, histological grade and subtype of the primary and the secondary cancers. Results: The mean age at diagnosis of the primary cervical cancer was 64 years. All of the patients had received definitive radiation therapy and chemotherapy. The mean latency period between the initial diagnosis of cervical cancer and the development of the endometrial carcinoma was 5.3 years. Two patients had stage I disease, one had stage II and one had stage III. Regarding the histological type, there was one case of endometrioid carcinoma, one of carcinosarcoma and two of serous carcinoma. All of the patients underwent hysterectomy and bilateral salpingo-oophorectomy and three received chemotherapy as adjuvant therapy. Three patients maintain their follow-up in our institution without any evidence of disease. Conclusion: Regular surveillance based on anamnesis and physical examination is of the most importance in women that underwent radiotherapy for cervical carcinoma. Imaging tests can aid in this particular subset of patients as cervical stenosis might hide an underlying condition. In our sample, only one patient complained of abnormal uterine bleeding and three patients had an aggressive histological type of endometrial cancer diagnosed. The latency period between the primary and secondary cancers was shorter than expected and might be related to small size of the sample.